Moody Teacher Ruins My Motivation: Students’ Voice on Effective EFL Teachers - Krisdayanty, Yuly; Hidayat, Muhamad Taufik; Dewi, Sinta (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2021)
Several problems appear in the educational field, one of which is teachers’ personality. Teacher’s personal trait is considered to be essential because it can affect students’ motivation in learning. However, some teachers remain unaware of its significance. It was evident in the students’ statements stating that they often had to learn with moody teachers who, as a result, ruined their learning motivation. The present study aims to explore the students’ perspectives on the EFL teacher’s personalities that influence the students’ motivation. To achieve the objective, the study utilized case study design in which the data were collected through semi-structured interview conducted to six senior high school students. The data were then analyzed by following Miles and Huberman’s (1994) framework. The results showed that all respondents shared agreement on the teacher’s personalities that they prefered. They felt happy and motivated when they learned with humble, friendly, kind, caring, patient, and humorous teachers. The results of this study may help the EFL teachers consider their personality as one of the vital aspects that could affect the students’ learning motivation. EFL teachers should pay more attention to their attitudes towards the students. In addition, the results suggest that policy makers should formulate rules that encourage teachers to not only focus on their hard skills but also their soft skills such as good personalities.